2019
DOI: 10.1097/rli.0000000000000600
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Guide to Artificial Intelligence–Based Image Analysis in Radiology

Abstract: The use of artificial intelligence (AI) is a powerful tool for image analysis that is increasingly being evaluated by radiology professionals. However, due to the fact that these methods have been developed for the analysis of nonmedical image data and data structure in radiology departments is not “AI ready”, implementing AI in radiology is not straightforward. The purpose of this review is to guide the reader through the pipeline of an AI project for automated image analysis in radiology and thereby encourag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 52 publications
0
50
0
1
Order By: Relevance
“…Artificial intelligence, including machine learning and deep learning, has been increasingly applied to medical imaging. 219 Promising results have been shown in various tasks related to radiological images, such as the detection of lesions, 220 segmentation (eg, labeling organs), 221 classification (eg, pneumonia vs cancer), 222 reconstruction (eg, MRI k-space to clinical image), 223 and noise reduction. 224 In relation to standardization of QIB, an AI algorithm that automates the process of QIB extraction has the capability to decrease variability, such as through an automated pipeline that can reduce ambiguity and variability in lesion segmentation.…”
Section: Artificial Intelligencementioning
confidence: 99%
See 1 more Smart Citation
“…Artificial intelligence, including machine learning and deep learning, has been increasingly applied to medical imaging. 219 Promising results have been shown in various tasks related to radiological images, such as the detection of lesions, 220 segmentation (eg, labeling organs), 221 classification (eg, pneumonia vs cancer), 222 reconstruction (eg, MRI k-space to clinical image), 223 and noise reduction. 224 In relation to standardization of QIB, an AI algorithm that automates the process of QIB extraction has the capability to decrease variability, such as through an automated pipeline that can reduce ambiguity and variability in lesion segmentation.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…There are several recommendations and guidelines for the development and evaluation of an AI algorithm in the medical field. 219 , 227 , 228 In brief, desired steps to develop a reliable AI algorithm include the following: (1) using reliable reference standards, (2) using a training dataset that matches the intended use, (3) tuning hyperparameters on a dataset independent of the training dataset, and (4) using external datasets to evaluate the model performance. To develop an AI algorithm that is robust to variability in acquisition parameters, machine settings, and clinical conditions, the algorithm should be trained with a heterogeneous dataset.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…Driven by increasing computing power and improving big data management, machine and deep learning-based convolutional neural networks (such as the Deep Convolutional Neural Network [DCNN]) can recognize and localize objects in medical images, 13 – 15 enabling disease characterization, tissue and lesion segmentation, and improved image reconstruction. 16 19 A single-center study using a homogenous dataset consisting of a standardized pulse sequence protocol from the same 3-T MRI scanner has shown that machine learning-based software can detect ACL tears with high accuracy.…”
mentioning
confidence: 99%
“…Increasing computing power and improved big data management have led to substantial advances of artificial intelligence (AI) [18,19]. Machine learning and deep learning are subcategories of the broader field of AI, which describe concepts of self-learning computer algorithms with the capability of solving specific tasks without being programmed with explicit rules [20,21]. In particular, great progress has been made in the field of image classification over the past decade.…”
Section: Introductionmentioning
confidence: 99%